Analisis Penerapan Undang-Undang Nomor 25 Tahun 2009 Tentang Pelayanan Publik di Sekretariat Daerah Kabupaten Bolaang Mongondow Utara - Talibo, Erwin; Akili, Rustam; Kasim, Ramdhan (Journal Evidence Of Law, 2023)
The purpose of the study was to find out the implementation of Law Number 25 of 2009 concerning Public Services in North Bolaang Monondow Regency. To find out what factors influence the implementation of Law Number 25 of 2009 in North Bolaang Mongondow Regency. In this study the authors used the Empirical research method. the authors conducted direct and structured research. The data analysis used in this research is qualitative analysis. Qualitative data is raw data from the empirical world. Qualitative data is raw data from the empirical world. Qualitative data is in the form of detailed descriptions, direct quotes and case documentation. So the problem is because in providing public services to the community has not implemented minimum standards so that many people feel that they have not received the services they should get. This situation causes the community as recipients or users of public services to be unsatisfied, causing many people to feel dissatisfied, so they are reluctant to take care of everything related to the government bureaucracy. As a result, there are many people who try to take shortcuts by violating existing regulations.